ADENOID AND TONSILLAR DYSFUNCTION AS A FACTOR IN IMPAIRMENT OF LOCAL AND SYSTEMIC IMMUNE DEFENSE IN CHILDREN - Dadamukhamedova Kh.E.,; Kholiyeva N.Kh.,; Berdiyev A.I., (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation. Adenoid and tonsillar dysfunction represents one of the leading causes of impaired mucosal and systemic immunity in childhood. This study investigates the immunological, microbiological, and structural alterations associated with chronic adenotonsillar pathology. A comparative analysis between hypertrophy cases and healthy controls was performed using immunological assays, cytokine profiling, and bacteriological evaluation. Children with adenotonsillar dysfunction demonstrated significant deficiencies in mucosal IgA production, altered T-cell distribution, and heightened inflammatory cytokine activity. The findings confirm that early detection and management of adenotonsillar disorders may significantly reduce recurrent respiratory illnesses and improve pediatric health outcomes.